PENGARUH GAYA KEPEMIMPINAN TRANSAKSIONAL TERHADAP PRESTASI DAN DISIPLIN KERJA DI PEMERINTAH DAERAH - Zebua, Reza (Merwin Publisher, 2025)
This study aims to explore the extent to which transactional leadership style affects employee job performance and work discipline within local government organizations. The research adopts a quantitative approach with a correlational design and simple linear regression analysis to examine the relationships between the independent variable (transactional leadership) and its dependent variables (job performance and work discipline). The sample comprises 200 respondents selected via stratified random sampling from relevant agencies within the local government environment. The instrument used is a measured questionnaire that has been validated for validity and reliability using Cronbach’s alpha and construct validity techniques. Data were analyzed using statistical software to compute the coefficient of determination, regression coefficients, and significance tests. The results indicate a positive and significant relationship between transactional leadership and job performance (p < 0.05) as well as work discipline (p < 0.05), though the magnitude of the influence is relatively moderate. These findings suggest the need for leadership development programs that balance task recognition with efforts to enhance workplace discipline in the public sector.